Analisis Color Grading dalam Menampilkan Adegan Flashback pada Film “Bebas” - Putri Nabila Tanjung; Dani Manesah (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
The analysis of the application of color grading in portraying flashback scenes in the film “Bebas”, focusing on how this technique influences viewers' perception of temporality and mood within the narrative. Color grading, as a process of manipulating colors in post-production, plays a significant role in distinguishing time periods and moods in a film. Through a qualitative approach, this study analyzes several scenes that use color grading to signify flashback moments in the film“Bebas”. The analysis involves identifying the color palettes used, the techniques applied, and their impact on the audience's experience. Color theory and the psychology of color serve as the foundation for understanding how colors affect emotions and temporal perception in films. This study aims to explore how this technique contributes to character development and the delivery of emotional messages. The findings indicate that the effective use of color grading in flashback scenes can create a clear distinction between the present and the past while evoking specific emotions aligned with the narrative context in the film “Bebas”.